Multidimensional signal and color image processing using lattices - Dubois, E. (John Wiley & Sons, Inc., 2019)
An Innovative Approach to Multidimensional Signals and Systems Theory for Image and Video Processing In this volume, Eric Dubois further develops the theory of multi-D signal processing wherein input and output are vector-value signals. With this framework, he introduces the reader to crucial concepts in signal processing such as continuous- and discrete-domain signals and systems, discrete-domain periodic signals, sampling and reconstruction, light and color, random field models, image representation and more. While most treatments use normalized representations for non-rectangular sampling, this approach obscures much of the geometrical and scale information of the signal. In contrast, Dr. Dubois uses actual units of space-time and frequency. Basis-independent representations appear as much as possible, and the basis is introduced where needed to perform calculations or implementations. Thus, lattice theory is developed from the beginning and rectangular sampling is treated as a special case. This is especially significant in the treatment of color and color image processing and for discrete transform representations based on symmetry groups, including fast computational algorithms. Other features include: -An entire chapter on lattices, giving the reader a thorough grounding in the use of lattices in signal processing -Extensive treatment of lattices as used to describe discrete-domain signals and signal periodicities -Chapters on sampling and reconstruction, random field models, symmetry invariant signals and systems and multidimensional Fourier transformation properties -Supplemented throughout with MATLAB examples and accompanying downloadable source code Graduate and doctoral students as well as senior undergraduates and professionals working in signal processing or videomage processing and imaging will appreciate this fresh approach to multidimensional signals and systems theory, both as a thorough introduction to the subject and as inspiration for future research.
Includes bibliographical references and index. - Online resource; title from digital title page (viewed on April 15, 2019)
Keywords: Signal processing; Lattice theory; Image processing -- Mathematics; Traitement du signal; Théorie des treillis; Traitement d'images; Mathématiques; TECHNOLOGY & ENGINEERING; Mechanical; Image processing; Mathematics